2007
DOI: 10.1002/ps.1403
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of resistance to pyriproxyfen in the Q biotype of Bemisia tabaci (Hemiptera: Aleyrodidae)

Abstract: Pyriproxyfen, a juvenile hormone (JH) mimic, is a biorational insecticide that disrupts insect development. It is one of the principal insecticides being used to control Bemisia tabaci (Gennadius) on cotton, and has many environmentally positive attributes that make it compatible with integrated pest management (IPM) programs. In Israel, a high level of resistance to pyriproxyfen has been observed in several isolated regions. Here, tests were conducted to establish whether temporal refuges from exposure to pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 48 publications
0
25
2
Order By: Relevance
“…The reduced relative fitness of the Pyri-SEL strongly indicates the fitness cost associated with development of resistance. Likewise, fitness cost associated with pyriproxyfen resistance has been reported in the Q biotype of B. tabaci [15]; however lack of fitness in B biotype of B. tabaci is also reported [54]. Development of insecticide resistance caused the selection of major genes that mostly leads to the disadvantageous biological parameters in the resistant species [55].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The reduced relative fitness of the Pyri-SEL strongly indicates the fitness cost associated with development of resistance. Likewise, fitness cost associated with pyriproxyfen resistance has been reported in the Q biotype of B. tabaci [15]; however lack of fitness in B biotype of B. tabaci is also reported [54]. Development of insecticide resistance caused the selection of major genes that mostly leads to the disadvantageous biological parameters in the resistant species [55].…”
Section: Discussionmentioning
confidence: 96%
“…It also is argued that the withdrawal of insecticide selection pressure led to diversion of resources from the fitness traits or alteration of the normal functioning of target site [28]. Reversion of resistance has been previously reported in a variety of insect pests against different insecticides [15,52]. Discontinued insecticide application with instable resistance portfolio (on discontinuing the selection pressure) may prove helpful to prolong the effective life span of such chemicals in the field.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A significant decrease in LC 50 values from F 0 to F 22 in the absence of pyriproxyfen selection showed that the alleles responsible for pyriproxyfen resistance seemed to be unstable. There are many reports of rapid reversion of resistance to insecticides in different insect pests without selection pressure when compared to the parental generation (Ferguson 2004;Pu et al 2010;Sial and Brunner 2012;Wilson et al 2007). The rate of reversion of resistance to insecticides can be influenced by major factors such as initial gene frequencies, relative fitness differences, and dominance relationships of alleles in the selected and susceptible counterpart strains (Roush and Croft 1986).…”
Section: Discussionmentioning
confidence: 98%
“…In our study, cqm1 REC frequency dropped from 0.99 in RIAB parental colony to 0.70 in F1, which was a direct effect of the introduction of susceptible individuals, and it remained stable throughout 11 generations, carried by heterozygous and resistant homozygous larvae. The cqm1 REC allele was not disfavored in the absence of selection pressure, unlike other studies in which resistance alleles have their frequency reduced, mainly due to biological costs (Tabashnik et al, 1994;Bourguet et al, 2004;Wilson et al, 2007;Anilkumar et al, 2008;Gassmann et al, 2009;Hardstone et al, 2009). Frequency of resistance allele was demonstrated by specific PCR which is an advantage over studies whose frequency have been indirectly estimated (Gassmann et al, 2009;Hardstone et al, 2009).…”
Section: Tablementioning
confidence: 90%